Shale oil mud based manganese modified mesoporous ceramsite as well as preparation method and application thereof
By preparing shale sludge-based manganese modified mesoporous ceramite, the problem of difficulty in removing thallium ions in the thallium-containing wastewater in the prior art is solved, and the efficient and low-cost thallium removal effect is achieved, and good regeneration performance and chemical stability are achieved.
Patent Information
- Application Number
- CN202510089468.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively remove thallium ions in thallium-containing wastewater, and traditional methods have problems such as weakening adsorption capacity, selectivity affected by competitive ions, and difficulty in regeneration and circulation.
Mesoporous ceramics with high adsorption capacity and specific selectivity are prepared by mixing raw materials such as shale sludge, coal gangue, etc. through drying, firing and manganese modification.
It achieves efficient removal of thallium in water, with better removal effect, higher specific selectivity, more effective regeneration ability and stronger chemical stability.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wastewater treatment and restoration, and specifically relates to a shale oil mud-based manganese-modified mesoporous ceramsite, a preparation method and application thereof. Background Art
[0002] In recent years, although the pace of development of the petrochemical industry has gradually slowed down, demand and consumption are still increasing, and it is still a pillar industry in today's world. While the petrochemical industry is developing, a large number of environmental pollution problems have been generated. During the extraction of oil, a large amount of oily sludge will be generated due to the operating process and treatment process. Oily sludge is generally a stable suspended emulsion system composed of water in oil (O / W), water in oil (W / O) and suspended matter. Oily sludge is divided into petroleum sludge and shale sludge according to different sources. Shale sludge is a semi-solid waste generated during the distillation of oil shale. It is very harmful to the environment. It has stable properties, a high degree of emulsification, and small sludge particles. Its components contain heavy metals such as Zn, Cd, Pb, Cr, Cu, Ni, Hg, as well as a large number of odorous and toxic substances such as benzene, phenols, polychlorinated biphenyls, dioxins, anthracene, and pyrene. The amount of shale sludge produced and stored is currently very huge in China. With the continuous development of the petroleum industry and the development of unconventional oil and gas fields, the amount of shale sludge produced is constantly increasing. Therefore, the harmless and resourceful treatment of shale sludge is imminent.
[0003] Mesoporous ceramsite is a new type of water treatment material that can effectively remove pollutants from water. This type of particle has many advantages, such as mesoporous structure and high surface area, which give them excellent adsorption capacity. The mesoporous structure can also efficiently filter pollutants such as heavy metals and dyes in water sources. It also has strong and regenerative properties, which can ensure its durability, stability and recyclability in various water treatment environments. The use of mesoporous ceramsite in water treatment processes can help develop sustainable and effective remediation solutions, providing tailored methods for treating specific pollutants and improving water quality. At present, many researchers are constantly improving the synthesis technology and optimizing the performance of mesoporous ceramsite, and their potential impact on the advancement of water treatment technology remains a focus of environmental sustainability.
[0004] Thallium-containing wastewater is produced in various industrial processes, such as lead and zinc mining, metal smelting, and electronic product production. Thallium is a highly toxic heavy metal that poses a serious threat to human health and the ecosystem. Due to its solubility, traditional wastewater treatment methods are ineffective and require advanced technologies such as ion exchange, adsorption, and precipitation to remove it. In view of the serious health hazards of thallium, my country currently has regulatory standards to control the discharge of thallium into water bodies.
[0005] There are many different technologies for treating thallium-containing wastewater. Ion exchange relies on resins to exchange thallium ions, but its regeneration and susceptibility to competing ions make it difficult to apply. Adsorption using materials such as activated carbon faces the problem of weakening adsorption capacity over time and selectivity being affected by other ions. Chemical precipitation and coagulation filtration are hampered by the formation of colloidal particles and changes in efficiency caused by pH and competing ions. Although bioremediation is environmentally friendly, it is sensitive to conditions and may require extended treatment times. Advanced oxidation processes are energy intensive and produce by-products that require further treatment. Membrane technology faces the challenges of scaling and high operating costs. Therefore, it is necessary to provide a new remediation material that has specific selectivity for thallium, little influence from competing ions, regenerative cycles, strong adsorption capacity, high efficiency, and low cost.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a method for preparing shale oil mud-based manganese-modified mesoporous ceramsite, and the preparation method comprises the following steps: (1) Drying, crushing and sieving shale oil sludge and coal gangue in sequence to obtain shale oil sludge powder and coal gangue powder; (2) The shale oil mud powder, the coal gangue powder, the diatomaceous earth powder, SiC and MgO are uniformly mixed to obtain a mixture; and the mixture is granulated by adding water to obtain mixed raw material balls; (3) drying the mixed raw material balls, firing them at high temperature and then cooling them to obtain mesoporous ceramsite; (4) The mesoporous ceramsite is subjected to surface manganese modification, and the process is completed.
[0008] Preferably, in step (1), the sieve used for sieving has an aperture of 100-200 mesh.
[0009] Preferably, the sieve used for screening has a mesh size of 100 meshes.
[0010] Preferably, in step (2), the weight ratio of shale oil mud powder, coal gangue powder, diatomaceous earth powder, SiC, and MgO is 68-72:13-17:13-17:3-5:0.3-0.5; And / or, the ratio of the mixture to water is 100 g: 28-30 mL; And / or, the particle size of the mixed raw material balls is 6-8 mm.
[0011] Preferably, in step (3), the drying temperature is 100-110° C. and the drying time is 2-3 h; And / or, the high temperature firing is divided into a preheating stage and a sintering stage, wherein: The preheating stage is to increase the temperature from room temperature to 650°C at a rate of 10°C / min and stay for 30 minutes; The sintering stage is to increase the temperature from 650°C to 1150°C at a rate of 10°C / min and stay for 25 minutes.
[0012] Preferably, in step (4), the mesoporous ceramsite is firstly immersed in a Mn(NO3)2 solution, then immersed in a Na2CO3 solution, and finally calcined.
[0013] Preferably, the concentration of the Mn(NO3)2 solution is 1.2-1.4 mol / L, and the immersion time in the Mn(NO3)2 solution is 4-5 h; and / or, the concentration of the Na2CO3 solution is 1.2-1.4 mol / L, and the immersion time in the Na2CO3 solution is 4-5 h; And / or, the calcination temperature is 460-500° C., and the calcination time is 2-4 hours.
[0014] Based on the same technical concept, the present invention also provides a shale oil mud-based manganese-modified mesoporous ceramsite obtained by the above preparation method.
[0015] Based on the same technical concept, the present invention also provides an application of shale oil mud-based manganese-modified mesoporous ceramsite in the field of removing heavy metals in water bodies, wherein the heavy metal is thallium.
[0016] For example, 99.9% thallium nitrate reagent is used to prepare thallium-containing wastewater with an initial concentration of 12 mg / L, and then the shale oil mud-based manganese-modified mesoporous ceramsite is placed in the solution at room temperature to remove thallium ions in the water.
[0017] The beneficial effects of the present invention are: The present invention selects oil sludge from oil and gas fields and coal gangue from mining areas as main raw materials, explores the preparation conditions for the original components of shale oil sludge and coal gangue, prepares mesoporous ceramsite, and then specifically performs manganese modification for thallium-containing wastewater to prepare a new adsorption material, provides a new high-efficiency and low-cost adsorbent for thallium repair technology, solves the problem of large-scale accumulation of solid wastes such as shale oil sludge, and achieves the ideal goal of "waste treatment with waste" environmental governance. The manganese-modified mesoporous ceramsite prepared by the present invention first contains manganese dioxide on the surface, which can react with thallium ions in water to undergo redox reactions, oxidizing I-valent thallium ions into easily treatable III-valent thallium ions, and secondly, the manganese-modified mesoporous ceramsite contains a variety of functional groups such as partial hydroxyl groups and carbon groups, which can interact with thallium ions in water to form coordination bonds, and the manganese-modified mesoporous ceramsite is a porous material, and the adsorption of heavy metals can also be achieved through two main methods of chemical adsorption and electrostatic action to achieve the purpose of removing thallium from water.
[0018] Compared with traditional mesoporous ceramsite, the manganese-modified mesoporous ceramsite prepared by the present invention has better removal effect, higher specific selectivity, more effective regeneration ability, stronger chemical stability and environmental friendliness in treating thallium-containing wastewater.
[0019] The manganese-modified mesoporous ceramsite prepared by the present invention was subjected to application tests, and the results showed that the manganese-modified ceramsite had a good removal effect on thallium in water. The removal of thallium in water by this adsorption material was mainly carried out through chemical adsorption, intraparticle diffusion and surface diffusion. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is the FTIR graph of the manganese-modified mesoporous ceramsite provided by the present invention.
[0022] Figure 2 The present invention provides a SEM image of manganese-modified mesoporous ceramsite; wherein: Figure 2 a in the figure is a SEM image with a scale of 50 μm; Figure 2 b is an enlarged view of a, with a scale bar of 10 μm; Figure 2 c is an enlarged view of b, with a scale bar of 5 μm; Figure 2 Image d is an enlarged view of image c, with a scale bar of 2.5 μm.
[0023] Figure 3 The present invention provides an XRD diagram of manganese-modified mesoporous ceramsite.
[0024] Figure 4 This is a data chart of the removal effect of thallium-containing wastewater at different pH values.
[0025] Figure 5 This is a data graph showing the removal effect of different initial concentrations on thallium-containing wastewater.
[0026] Figure 6 This is a data chart showing the removal effect of different dosages on thallium-containing wastewater.
[0027] Figure 7 This is a data graph showing the removal effect of thallium-containing wastewater at different adsorption times.
[0028] Figure 8 This is a data graph showing the removal effect of thallium-containing wastewater at different adsorption temperatures.
[0029] Fig. 9 It is a pseudo-first-order kinetic data diagram.
[0030] Fig.10 It is a pseudo-second-order kinetic data graph.
[0031] Fig.11 It is the data graph of the intra-particle diffusion model fitting.
[0032] Fig.12 It is the Langmuir model fitting diagram.
[0033] Fig.13 It is the Freundlich model fitting diagram.
[0034] Fig.14 This is a graph showing the effect of different solution concentrations and times on the desorption effect when the desorbent is HCl.
[0035] Fig.15 This is a graph showing the influence of different solution concentrations and times on the desorption effect when the desorbent is NaOH.
[0036] Fig.16 This is a data graph showing the influence of the number of desorption times.
[0037] Fig.17 This is a data chart showing the effects of lead and zinc ions on manganese-modified expanded clay on thallium-containing wastewater. DETAILED DESCRIPTION
[0038] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0039] Example 1 This embodiment provides a method for preparing shale oil mud-based manganese-modified mesoporous ceramsite, the preparation method comprising the following steps: (1) Drying, crushing, and passing through a 100-mesh sieve respectively and the shale oil sludge and coal gangue to obtain shale oil sludge powder and coal gangue powder; (2) 68 g of shale oil mud powder, 13 g of coal gangue powder, 13 g of diatomaceous earth powder, 3 g of SiC, and 0.3 g of MgO were mixed uniformly to obtain a mixture; water was then added to the mixture and granulated by hand to obtain mixed raw material balls with an average particle size of 6 mm; (3) The mixed raw material balls are moved into an oven, dried at 100° C. for 3 h, and then fired in a muffle furnace and cooled to obtain mesoporous ceramsite; wherein the firing is divided into a preheating stage and a sintering stage: The preheating stage is to increase the temperature from room temperature to 650°C at a rate of 10°C / min and stay for 30 minutes; The sintering stage is to increase the temperature from 650°C to 1150°C at a rate of 10°C / min and stay for 25 minutes; (4) The mesoporous ceramsite is immersed in a 1.2 mol / L Mn(NO3)2 solution for modification for 5 h, dried and immersed in a 1.2 mol / L Na2CO3 solution for modification for 5 h, and finally dried and placed in a muffle furnace for calcination at 460°C for 4 h. After natural cooling, shale oil mud-based manganese-modified mesoporous ceramsite is obtained.
[0040] Example 2 This embodiment provides a method for preparing shale oil mud-based manganese-modified mesoporous ceramsite, the preparation method comprising the following steps: (1) Drying, crushing, and passing through a 200-mesh sieve respectively and the shale oil sludge and coal gangue to obtain shale oil sludge powder and coal gangue powder; (2) 72 g of shale oil mud powder, 17 g of coal gangue powder, 17 g of diatomaceous earth powder, 5 g of SiC, and 0.5 g of MgO were mixed uniformly to obtain a mixture; water was then added to the mixture and granulated by hand to obtain mixed raw material balls with an average particle size of 8 mm; (3) The mixed raw material balls are moved to an oven, dried at 110° C. for 2 h, and then fired in a muffle furnace and cooled to obtain mesoporous ceramsite; wherein the firing is divided into a preheating stage and a sintering stage: The preheating stage is to increase the temperature from room temperature to 650°C at a rate of 10°C / min and stay for 30 minutes; The sintering stage is to increase the temperature from 650°C to 1150°C at a rate of 10°C / min and stay for 25 minutes; (4) The mesoporous ceramsite is immersed in a 1.4 mol / L Mn(NO3)2 solution for modification for 4 h, dried and immersed in a 1.4 mol / L Na2CO3 solution for modification for 4 h, and finally dried and calcined in a muffle furnace at 500°C for 2 h. After natural cooling, shale oil mud-based manganese-modified mesoporous ceramsite is obtained.
[0041] Example 3 This embodiment provides a method for preparing shale oil mud-based manganese-modified mesoporous ceramsite, the preparation method comprising the following steps: (1) Drying, crushing, and passing 150-mesh sieves on shale oil sludge and coal gangue, respectively, to obtain shale oil sludge powder and coal gangue powder; (2) 70 g of shale oil mud powder, 15 g of coal gangue powder, 15 g of diatomaceous earth powder, 4 g of SiC, and 0.4 g of MgO were mixed uniformly to obtain a mixture; water was then added to the mixture and granulated by hand to obtain mixed raw material balls with an average particle size of 7 mm; (3) The mixed raw material balls are moved to an oven, dried at 105° C. for 2 h, and then fired in a muffle furnace and cooled to obtain mesoporous ceramsite; wherein the firing is divided into a preheating stage and a sintering stage: The preheating stage is to increase the temperature from room temperature to 650°C at a rate of 10°C / min and stay for 30 minutes; The sintering stage is to increase the temperature from 650°C to 1150°C at a rate of 10°C / min and stay for 25 minutes; (4) The mesoporous ceramsite is immersed in a 1.3 mol / L Mn(NO3)2 solution for modification for 4 h, dried and immersed in a 1.3 mol / L Na2CO3 solution for modification for 4 h, and finally dried and placed in a muffle furnace for calcination at 480°C for 3 h. After natural cooling, shale oil mud-based manganese-modified mesoporous ceramsite is obtained.
[0042] Characterization example The shale oil mud-based manganese-modified mesoporous ceramsite obtained in Example 1 was characterized by infrared spectroscopy. Figure 1 As shown by Figure 1 It can be seen that the stretching vibration peak of hydrogen bond OH is at a wave number of 3442 cm -1 The presence of hydroxyl groups at wave numbers 2924 and 2852 cm -1 The peak at is related to the CH stretching vibration; the C=О stretching vibration peak appears at a wave number of 1636cm -1 The CH bending vibration peak is at a wave number of 1384 cm -1 The CO stretching vibration peak appears at a wave number of 1073 cm -1 Appear at 777cm -1 and 668cm -1 The peak at 467 cm is related to metal-oxygen vibration, which may indicate the presence of Mn-O bonds; the bending vibration of Si-O bonds causes -1 In summary, the FTIR spectrum results show that there are hydroxyl, aliphatic hydrocarbon, carbonyl, CH or OH bond bending vibration, CO stretching vibration and metal oxygen vibration on the surface of manganese-modified mesoporous ceramsite. These findings are consistent with the results of modification, because the modification process introduces metal oxygen bonds, which may change the organic and inorganic components of the material.
[0043] The shale oil mud-based manganese-modified mesoporous ceramsite obtained in Example 1 was characterized by SEM electron microscopy, and the results are as follows: Figure 2 As shown by Figure 2It can be seen that the surface morphology and internal structure information of manganese-modified mesoporous ceramsite were obtained by SEM scanning electron microscopy. Figure 2 It can be observed that the surface and interior of the manganese-modified mesoporous ceramsite show relatively obvious regular square lattice crystals. These crystals are not common on the surface of mesoporous ceramsite, so they are inferred to be MnO2. This observation is also consistent with the characteristics of MnO2, further proving the successful implementation of manganese-modified mesoporous ceramsite.
[0044] The shale oil mud-based manganese-modified mesoporous ceramsite obtained in Example 1 was characterized by XRD. The results are as follows: Figure 3 As shown by Figure 3 It can be seen that the main phases of manganese-modified mesoporous ceramsite are SiO2, SiC, and MnO2, which is consistent with the basic properties of the material.
[0045] Test Case (I) Factors affecting the removal of thallium-containing wastewater by manganese-modified mesoporous ceramsite (obtained in Example 1) 1. Effect of pH value In the water sample with the initial concentration of 12 mg / L of Tl-containing wastewater, the pH value was adjusted to 3, 5, 7, 9, and 11, and 30 g / L of manganese-modified ceramsite was added, and then oscillated at room temperature (150 r / min) for 5 h. The results are as follows Figure 4 shown.
[0046] Depend on Figure 4 It can be seen that within a certain pH range, the removal rate of Tl by manganese-modified ceramsite is between 75.8% and 82.4%, and the adsorption amount is between 0.29 and 0.31 mg / g, which changes with the change of pH. When the pH is about 3, the removal rate of Tl by manganese-modified ceramsite is the largest (82.39%), indicating that under strong acidic conditions, manganese-modified ceramsite is conducive to the treatment of thallium-containing wastewater, while under alkaline conditions, it is the opposite. The reason is that the adsorption of thallium by manganese oxide is to oxidize Tl (I) to Tl (III), and then remove it by adsorption. In the low pH range, the rich H + It can promote the redox reaction, oxidize the adsorbed Tl (I) to Tl (III), and further deposit on the surface of manganese-modified ceramsite. Under alkaline conditions, it may be because the potential of manganese dioxide changes, resulting in changes in its redox properties, which affects its oxidation and adsorption capacity for Tl, resulting in a decrease in Tl removal rate.
[0047] 2. Effect of initial concentration In the water samples with initial Tl concentrations of 4, 8, 12, 16, and 20 mg / L in simulated Tl-containing wastewater, the pH value was adjusted to 3, and 30 g / L of manganese-modified ceramsite was added respectively. After oscillation (150 r / min) at room temperature for 5 h, the following results were obtained. Figure 5 shown.
[0048] Figure 5 In the initial Tl concentration range of 4~20 mg / L, after 5h of adsorption, the Tl removal rate of manganese-modified expanded clay was in the range of 71.25%~82.98%, and the adsorption amount was in the range of 0.11~0.49 mg / g. On the whole, with the increase of Tl concentration, the adsorption amount gradually increased, but the removal rate gradually decreased. The reason for this phenomenon is that the adsorption sites provided by expanded clay are fixed. As the solution concentration increases, the adsorption sites are constantly occupied, and the remaining Tl cannot be further adsorbed.
[0049] 3. Influence of dosage In the water sample with the initial concentration of Tl in the simulated Tl-containing wastewater of 12 mg / L, the pH value was adjusted to 3, and 10, 20, 30, 40, and 50 g / L of manganese-modified ceramsite were added respectively. After oscillation (150 r / min) at room temperature for 5 h, the following results were obtained. Figure 6 shown.
[0050] Depend on Figure 6 As shown in the figure, within a certain dosage range, after 5 hours of adsorption by manganese-modified expanded clay, the removal rate of Tl ranged from 42.04 to 80.91%, and the adsorption amount was 0.26 to 0.62 mg / g. Under the same initial concentration conditions, with the increase of the amount of manganese-modified expanded clay, the adsorption amount decreased and the removal rate gradually increased. The main reason is that when the initial concentration of Tl is constant, with the increase of dosage, more adsorption sites and surface active groups are provided, and the probability of reaction with Tl will increase, thereby increasing the removal rate.
[0051] 4. Influence of adsorption time The pH value of 12mg / L LTL wastewater was adjusted to 3, 30g / L manganese modified ceramsite was added, and the mixture was shaken at room temperature (150r / min) for 1, 3, 5, 7, and 9h, and the following results were obtained. Figure 7 shown.
[0052] Depend on Figure 7 It can be seen that within a certain time range, the removal rate of Tl by manganese-modified ceramsite ranges from 63.9% to 82.67%, and the adsorption amount ranges from 0.24 to 0.32 mg / g. On the whole, at the same initial concentration and dosage, the longer the time, the greater the adsorption amount and removal rate, indicating that the longer the adsorption reaction time, the better the Tl removal effect. The reason is that the thallium ions in the wastewater can diffuse more fully to the adsorption sites of the ceramsite, thereby enhancing the adsorption effect. Secondly, the surface active sites and functional groups of manganese-modified ceramsite react more thoroughly with the thallium ions in the thallium-containing wastewater.
[0053] 5. Influence of adsorption temperature In the wastewater containing 12 mg / L Tl, the pH value was adjusted to 3, 30 g / L manganese modified ceramsite was added, and the temperature was 20, 25, 30, 35, 40 ° C. After oscillation (150 r / min) for 5 hours, the following results were obtained. Figure 8 shown.
[0054] Depend on Figure 8 It can be seen that within a certain temperature range, the removal rate of manganese-modified ceramsite for Tl ranges from 85.25% to 86.71%, and the adsorption amount is 0.327 to 0.334 mg / g, with a small overall fluctuation, indicating that temperature has little effect on the adsorption of Tl by manganese-modified ceramsite. The reason may be that within this temperature range, the kinetics and thermodynamics of the adsorption process are relatively stable, resulting in a low sensitivity of the adsorption process to temperature, making the change in removal effect less significant. It may also be because the adsorption sites on the surface of manganese-modified ceramsite are relatively stable within this temperature range, and are not affected by temperature changes or are less affected. Therefore, the change in temperature has little effect on the removal effect. In practical applications, considering the energy consumption of water treatment, it is generally treated at room temperature.
[0055] 6. Summary Based on the surface response method (RSM), it was found that the optimal conditions for the removal of thallium-containing wastewater by manganese-modified mesoporous ceramsite are as follows: when the pH value is around 3.79, the dosage is 53.53 g / L, the adsorption time is 9.90 h, and the temperature is 25°C, the thallium removal rate can reach 94.97%.
[0056] (II) Analysis of adsorption mechanism (using the manganese-modified mesoporous ceramsite obtained in Example 1 as the test object) 1. Adsorption kinetics model 1.1 Pseudo-first-order kinetics Depend on Fig. 9 It can be seen that the correlation coefficient R of pseudo-first-order adsorption kinetics 2 reached 0.96132, however, the calculated adsorption amount (q e ) and the actual adsorption amount (qe exp ) are significantly different. When the initial concentration is 12 mg / L, the calculated result differs from the experimental value by 0.2225 mg / g, which is a large error. It is inferred that the pseudo-first-order adsorption kinetic equation is not accurate to describe the adsorption behavior of Tl by modified ceramsite.
[0057] 1.2 Pseudo-second-order kinetics Depend on Fig.10 It can be seen that by fitting the kinetic equation of Tl adsorption in water by manganese-modified ceramsite, R 2 is 0.99335, and the calculated q e Compared with the experimentally obtained qe expThere is little difference, only 0.0266 mg / g between the two, which shows that the pseudo-second-order adsorption kinetic equation is more accurate in describing the adsorption behavior of Tl by manganese-modified ceramsite.
[0058] The pseudo-second-order kinetics is significantly better than the pseudo-first-order kinetics, indicating that the adsorption process is affected by multiple reaction steps, rather than just a simple adsorption reaction. This means that the adsorption process involves the formation of complex surface intermediates or multi-step reactions, rather than just a simple chemical reaction between the adsorbate and the adsorption surface. Therefore, more factors need to be considered to describe and understand the adsorption behavior.
[0059] 1.3 Internal diffusion model like Fig.11 As shown in the figure, the correlation coefficient of the intraparticle diffusion model is 0.95768. The fitting curve of particle diffusion is linear, indicating that intraparticle diffusion is the rate-controlling step. However, the curve fitted by the model does not pass through the origin, indicating that the actual diffusion behavior does not match the behavior assumed by the model, which means that intraparticle diffusion is not the only rate-controlling step.
[0060] After summary, the above adsorption kinetic parameters are shown in Table 1.
[0061] Table 1 Adsorption kinetic parameters
[0062] In general, the pseudo-second-order kinetics R 2 R is better than pseudo-first-order kinetics and intraparticle diffusion models 2 , which shows that the explanation of the adsorption process involves not only the rate control of the chemical reaction, but also the influence of surface diffusion.
[0063] 2. Adsorption isotherm model From Table 2 and Fig.12 As shown in Table 2, the correlation coefficient of the Langmuir model fitting is 0.98267; Fig.13 As shown, the correlation coefficient of the Freundlich model fitting is 0.99058. Relatively speaking, the fitting effect of the Freundlich model is better, and it confirms the fact that Tl is attached to the surface of the ceramsite in a multi-layer adsorption manner. The 1 / n value in the Freundlich model represents the degree of non-uniformity of adsorption, and the n value is usually between 0-1. When the temperature is 25°C, the 1 / n value is 0.64, which is greater than 0.5. At this time, it can be understood that the solid adsorbent has a strong affinity for the substance to be adsorbed, and the adsorption process is relatively uniform. In this case, manganese-modified ceramsite can more effectively adsorb Tl, and the adsorption capacity is relatively stable.
[0064] Table 2 Adsorption model fitting parameters
[0065] (III) Desorption and regeneration of manganese-modified ceramsite (obtained in Example 1) 1. Effect of desorbent, concentration and time on desorption effect The manganese-modified ceramsite treated with thallium-containing wastewater under the optimized removal conditions of the RSM method was placed in HCl and NaOH solutions with desorption concentrations of 0.5, 1, and 2 mol / L for 1, 3, and 5 hours, respectively. The following results were obtained after treating the thallium-containing wastewater: Fig.14 , Fig.15 Results shown.
[0066] Depend on Fig.14 It can be seen that when the concentration of HCl desorbent is in the range of 0.5~2mol / L, after desorption for 1, 3, and 5h, the removal rates of Tl by manganese-modified ceramsite are 88~91.16%, 90~94.08%, and 87~93.33%, respectively. The desorption effect is better at 3h. Too short a time may cause incomplete desorption, and too long a time may damage the adsorption performance of the manganese-modified ceramsite itself. From the perspective of desorbent concentration, there is an overall downward trend, indicating that the desorption effect is good under low concentration conditions. Too high a desorbent concentration causes the manganese-modified ceramsite itself to be more corrosive, affecting the adsorption performance.
[0067] Depend on Fig.15 It can be seen that when the concentration of NaOH desorbent is in the range of 0.5~2mol / L, after desorption for 1, 3, and 5h, the removal rates of Tl by manganese-modified ceramsite are 86.92~92.33%, 91.67~93.67%, and 91.75~93.08%, respectively. Overall, the desorption effect is better at 3h; from the perspective of desorbent concentration, it shows an overall upward trend, which means that the desorption effect is better under conditions of high alkaline concentration, and incomplete desorption may occur under low concentration conditions.
[0068] In summary, from the perspective of economy and environmental protection, compared with NaOH solution, HCl desorbent has a lower required concentration and better desorption effect, because in acidic solution, H+ will compete with the ceramsite for the adsorption of metal ions, thereby replacing the Tl ions in the manganese-modified ceramsite. Therefore, the optimal desorption condition is to use 0.5 mol / L HCl for desorption for 3 hours.
[0069] 2. The influence of desorption times on desorption regeneration effect The thallium was desorbed by manganese-modified ceramsite under the optimal desorption conditions, and then re-adsorbed under the conditions of initial concentration of 12 mg / L, pH of 3.8, adsorption time of 9.89 h, and temperature of 25 °C. Then, the removal rate of each adsorption was used as an indicator, and the adsorption and desorption were carried out 6 times. The results are as follows Fig.16 shown.
[0070] according to Fig.16As shown in the figure, with the increase of the number of adsorption-desorption cycles, the Tl removal efficiency gradually decreases. It may be that the surface of the ceramsite is damaged during the adsorption and desorption process, resulting in its own mass loss and structural changes. When the number of desorptions is less than 3 times, the Tl removal rate is still high, which is 94.00%, 88.19% and 86.15% respectively; starting from the fourth desorption, the Tl removal rate of the ceramsite decreases to 78.41%, 71.91% and 68.21% respectively, with a large decline. Considering the mass loss of ceramsite, with the increase of the number of desorptions, the mass loss of the ceramsite itself will also increase. When the number of desorptions does not exceed 3 times, the mass loss of the ceramsite itself is small and remains below 5%. If the number of desorptions increases to 6 times, the mass loss of the ceramsite will reach 7.86%. Therefore, in order to ensure the Tl removal rate and actual availability, it is not advisable to recycle the ceramsite too much.
[0071] (IV) Effect of simulated competitive ion pairs on manganese-modified ceramsite (obtained in Example 1) on thallium-containing wastewater Under the optimal removal conditions, manganese-modified ceramsite was used as the adsorption material and was put into a mixture of thallium and lead, a mixture of thallium and zinc, and a mixture of thallium, lead and zinc. The adsorption was carried out under the same conditions of other influencing factors. The removal rates of thallium, lead and zinc by manganese-modified ceramsite were calculated and tested. The results are as follows: Fig.17 shown.
[0072] Depend on Fig.17 It can be seen that the competitive adsorption of Pb and Zn ions with Tl has a small overall effect. Under the optimal conditions, the removal rate of manganese-modified ceramsite for thallium-containing wastewater is 94.97%; in the mixed solution of Tl and Pb, the removal rate of Tl decreased by 16.47%; in the mixed solution of Tl and Pb, the removal rate of Tl decreased by 16.47%; in the mixed solution of Tl and Zn, the removal rate of Tl decreased by 18.93%; in the mixed solution of Tl, Pb and Zn, the removal rate of Tl decreased by 7.8%; in the case of the coexistence of the three, it may be because of the competitive adsorption of lead and zinc. Overall, the presence of lead and zinc ions has little effect on manganese-modified ceramsite on thallium-containing wastewater, indicating that manganese-modified ceramsite has a certain selectivity in the adsorption of thallium.
[0073] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing shale oil mud-based manganese-modified mesoporous ceramsite, characterized in that: The preparation method comprises the following steps: (1) Drying, crushing and sieving shale oil sludge and coal gangue in sequence to obtain shale oil sludge powder and coal gangue powder; (2) uniformly mixing the shale oil mud powder, the coal gangue powder, the diatomaceous earth powder, SiC and MgO to obtain a mixture; then adding water to the mixture to granulate the mixture to obtain mixed raw material balls; (3) drying the mixed raw material balls, firing them at high temperature and then cooling them to obtain mesoporous ceramsite; (4) The mesoporous ceramsite is subjected to surface manganese modification, and the process is completed.
2. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 1, characterized in that: In step (1), the sieve used for sieving has an aperture of 100-200 meshes.
3. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 2, characterized in that: The sieve used for the screening has a mesh size of 100 meshes.
4. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 1, characterized in that: In step (2), the weight ratio of shale oil mud powder, coal gangue powder, diatomaceous earth powder, SiC and MgO is 68-72:13-17:13-17:3-5:0.3-0.5; And / or, the ratio of the mixture to water is 100 g: 28-30 mL; And / or, the particle size of the mixed raw material balls is 6-8 mm.
5. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 1, characterized in that: In step (3), the drying temperature is 100-110°C and the drying time is 2-3 hours; And / or, the high temperature firing is divided into a preheating stage and a sintering stage, wherein: The preheating stage is to increase the temperature from room temperature to 650°C at a rate of 10°C / min and stay for 30 minutes; The sintering stage is to increase the temperature from 650°C to 1150°C at a rate of 10°C / min and stay for 25 minutes.
6. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 1, characterized in that: In step (4), the mesoporous ceramsite is firstly immersed in a Mn(NO3)2 solution, then immersed in a Na2CO3 solution, and finally calcined.
7. The method for preparing shale oil mud-based manganese-modified mesoporous ceramsite according to claim 6, characterized in that: The concentration of the Mn(NO3)2 solution is 1.2-1.4 mol / L, and the immersion time in the Mn(NO3)2 solution is 4-5 h; and / or, the concentration of the Na2CO3 solution is 1.2-1.4 mol / L, and the immersion time in the Na2CO3 solution is 4-5 h; And / or, the calcination temperature is 460-500° C., and the calcination time is 2-4 hours.
8. Shale oil mud-based manganese-modified mesoporous ceramsite obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the shale oil mud-based manganese-modified mesoporous ceramsite according to claim 8 in the field of removing heavy metals from water bodies.
10. The use according to claim 9, characterized in that: The heavy metal is thallium.
Citation Information
Patent Citations
Hydrated metal oxide loaded porous ceramisite adsorption material and preparation method
CN108404857A
Nanometer activated porous composite ceramisite based water dephosphorization technology
CN108439522A
Soil heavy metal lead fixation method by vermiculite loaded nano Fe-based material
CN109821878A
Modified ceramsite with functions of controlling phosphorus and suppressing algae, and preparation method and application thereof
CN110698225A
Ceramsite catalyst for sewage treatment as well as preparation method and application method thereof
CN111468106A
Cited By
Oil shale waste nano-composite adsorbent as well as preparation method and application thereof
CN121513808A